Keluarga Sakinah Mawaddah Wa Rahmah Menurut Al-Qur’an Perspektif Wahbah Az-Zuhaili - Ririn Andriani; Hasan Zaini (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Based on a vast social phenomenon that craves and praises perfect, perfect families. Yet many do not know what the perfect family represents, what its purpose is, what its criteria are and how to do it. The purpose of this research is: (1) to describe and analyze what the purpose and criteria of the family sakinah mawaddah wa rahmah according to the al-qur'an wahbah az-zuhaili perspective. (2) to describe and analyze how to realize the family of sakinah mawaddah wa rahmah according to the al-qur'an wahbah az-zuhaili perspective. The study included research for literature (library research) by means of thematic or maudhu 'i interpretation analysis.